Dairy cattle traits preference ranking to define a balanced breeding objective for small and large dairy farms in Ethiopia highlands - Aliy, M.; Kebede, K.; Meseret, Selam; Gebreyohanes, Gebregziabher; Mrode, Raphael A.; Lidauer, M.H.; Okeyo Mwai, Ally; Urge, M.; Negussie, E. (2026)
Background: A study defining breeding goal traits pertinent to the smallholder and large commercial dairy farms in Ethiopian highlands is limited. Accordingly, this study was designed to identify the most important dairy cattle traits to be incorporated into breeding objectives for dairy cattle herds belonging to the small and large commercial farms in Ethiopian highlands.